The effect of soy milk on haemoglobin levels in pregnant women with anaemia - Sugiarsih, Ugi; Solihah, Eneng; Budiarti, Yati (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: Anaemia is one of the health problems that occur in pregnant women, often associated with a lack of iron intake. One approach to overcoming iron deficiency anaemia is through the use of functional foods, such as soy milk, because it contains high protein and iron, which can stimulate the production of red blood cells. This study aims to determine the effect of soy milk on haemoglobin levels in pregnant women with anaemia. This research method uses a quasi-experimental research design with a pretest-posttest control group design. The intervention group underwent an initial haemoglobin level check (Haemoglobin 1), followed by a 15-day intervention period by consuming soy milk (250 ml/day) and Fe tablets (2x1/day). On day 16, the haemoglobin level was re-evaluated (Haemoglobin 2). Meanwhile, the control group also underwent an initial haemoglobin level check (Haemoglobin 1) and then received iron tablets (2x1/day), with a follow-up haemoglobin level check on day 16 (Haemoglobin 2). The total sample size was 130 people (65 people in the intervention group and 65 people in the control group). Sampling was purposive sampling, and the data were analysed with a dependent t-test for the intervention group, a Wilcoxon test for the control group, and a Mann-Whitney test. The majority of respondents were between 20 and 35 years old (94.6%), had junior high school education (63.15%), did not work (75.4%), had a had a parity less than 2 (76.9%), and had a had a low knowledge level (70.8%). After the intervention, haemoglobin levels increased by 0.9. Statistical analysis showed a significant difference in the mean haemoglobin levels before and after soy milk consumption (p = 0.001). In addition, there was a significant difference in haemoglobin levels between the intervention group and the control group (p = 0.001). Soy milk consumption showed a positive effect on haemoglobin levels in anaemic pregnant women. Soy milk consumption (2x250 ml/day) can be an alternative to increasing haemoglobin levels in pregnant women.